2019
DOI: 10.1021/acsbiomaterials.9b00920
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate Cross-Linked Small Intestinal Submucosa for Guided Bone Regeneration

Abstract: Collagen membranes are widely used in guided bone regeneration (GBR) because of their good biocompatibility and low immunogenicity. As a bioderived collagen membrane, small intestinal submucosa (SIS) has good regenerative potential for soft tissue repair, but it lacks sufficient mechanical properties for GBR application unless properly modifided. Epigallocatechin-3-gallate (EGCG) is a natural cross-linking agent featuring osteoinductive activity. In this study, we modified SIS by EGCG cross-linking, and such m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…4). Previous studies have reported that pore sizes below 50 μm in collagen sponges promote osteoconduction 21,33) . Given these results, although small pores of c.a.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…4). Previous studies have reported that pore sizes below 50 μm in collagen sponges promote osteoconduction 21,33) . Given these results, although small pores of c.a.…”
Section: Discussionmentioning
confidence: 96%
“…Generally, the pore size is known to alter the bone-forming ability of materials 32) , and the optimal pore size of calcium phosphate-based materials for bone regeneration is recognized to be over 100 μm 32) . However, the adequate pore size of polymer-based sponges for bone regeneration remains unclear because the immersion of materials in body fluid causes swelling, thereby changing the pore size 21) . In fact, both NC-and AC-vhEGCG-GSs could induce bone formation in the center of defects (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Known as a condensed tannin, PC consist of oligomer or polymers of (epi) catechin, whose phenolic hydroxyl structures have the capacity to form intermolecular hydrogen bonds. Unlike epigallocatechin gallate (EGCG), a catechin monomer with pro-osteogenesis activity [ 44 ], PC has anti-calcification activity which is favorable for bladder repair. In this study, PC was tested as a crosslinking agent for SIS membrane to generate a cell-free scaffold for their potential for bladder reconstruction.…”
Section: Discussionmentioning
confidence: 99%